Aluminium SHS and RHS subjected to biaxial bending: Experimental testing, modelling and design recommendations. (15th January 2021) - Bock, Marina; Theofanous, Marios; Dirar, Samir; Lipitkas, Nikolaos
Highlights: Material and four point bending tests on aluminium alloy sections are reported. The bending tests included major axis, minor axis and biaxial bending. A numerical model is developed and validated against the reported test results. Current Eurocode 9 design approach for biaxial bending is assessed and found conservative. A new design methodology based on the continuous strength method is developed. Abstract: Traditionally, experimental research on structural members has focused on the isolated fundamental cases of pure compression/tension, major axis bending or minor axis bending, whilst beam columns under compression and uniaxial bending have also been tested. Biaxial bending has received less experimental attention and it has always been assumed that tests on the idealised cases of major axis bending and minor axis bending can be used together with numerical predictions of biaxial bending to determine suitable interaction curves. This investigation reports an experimental study on aluminium flexural members with variable angles between the plane of bending and the major axis of the cross-section. Cross-sections with various thicknesses and hence plate slenderness values are considered. The experimental results are used to validate a numerical model that allows a large number of cross-sectional dimensions and loading cases to be examined. Following parametric studies and generation of numerical data, the design provisions for biaxial bending specified in EN 1999-1-1 are compared against the predictions provided by the Continuous Strength Method (CSM) and a new proposed method. The comparison shows that EN 1999-1-1 provides overly conservative results with biaxial bending resistances underestimated by approximately 17%. Both the CSM and the proposed method are observed to significantly improve predictions by reducing, on average, underestimations down to 3% and 1%, respectively, and consequently enabling a better usage of the material and ultimately a more economic and sustainable design.